Architectural elements of traditional Malay buildings in Gombak district, Selangor - Salleh, Nurul Hamiruddin; Abdullah, Mohammad Zaim; Ab Jalil, Nurlelawati (IIUM Press, 2023)
Every traditional Malay building has its historical roots representing its predominant local identity, belief and culture and is often associated with a specific state. Unlike many states in Malaysia, the architectural identity of traditional Malay buildings in Selangor is relatively scarce and henceforth requires more explicit characteristic mapping. There are at least fifteen (15) common decorative elements identified within the traditional Malay buildings in Malaysia, namely tunjuk langit, sisik naga, sulur bayung, ande-ande, papan pemeleh, kepala cicak, tiang gantung, kekisi, gerbang, gerbang pintu, sesiku keluang, kepala pintu, kepala tingkap and pagar musang. The main objective of this research is to identify the architectural decorative elements of the traditional Malay houses and masjids in the Gombak district, Selangor. Onsite observations were conducted on the thirty-nine (39) traditional Malay buildings (34 houses and 5 masjids) in thirteen (13) villages of Gombak. The research identified eight (8) common architectural elements in Gombak's traditional Malay houses and masjids. The architectural elements enrich the aesthetical theory and philosophy of the traditional Malay houses and masjids in Selangor as well as in Malaysia and shall be preserved.